Nrf2-Mediated Antioxidant Defense and Thyroid Hormone Signaling: A Focus on Cardioprotective Effects - Laura Sabatino (MDPI AG, 2023)
Thyroid hormones (TH) perform a plethora of actions in numerous tissues and induce an overall increase in metabolism, with an augmentation in energy demand and oxygen expenditure. Oxidants are required for normal thyroid-cell proliferation, as well as for the synthesis of the main hormones secreted by the thyroid gland, triiodothyronine (T3) and thyroxine (T4). However, an uncontrolled excess of oxidants can cause oxidative stress, a major trigger in the pathogenesis of a broad spectrum of diseases, including inflammation and cancer. In particular, oxidative stress is implicated in both hypo- and hyper-thyroid diseases. Furthermore, it is important for the TH system to rely on efficient antioxidant defense, to maintain balance, despite sustained tissue exposure to oxidants. One of the main endogenous antioxidant responses is the pathway centered on the nuclear factor erythroid 2-related factor (Nrf2). The aim of the present review is to explore the multiple links between Nrf2-related pathways and various TH-associated conditions. The main aspect of TH signaling is described and the role of Nrf2 in oxidant-antioxidant homeostasis in the TH system is evaluated. Next, the antioxidant function of Nrf2 associated with oxidative stress induced by TH pathological excess is discussed and, subsequently, particular attention is given to the cardioprotective role of TH, which also acts through the mediation of Nrf2. In conclusion, the interaction between Nrf2 and most common natural antioxidant agents in altered states of TH is briefly evaluated.